Market acceptability and accelerated shelf-life testing of improved squash-corn chips - Atienza, Maria Laura B.
Squash-corn ships obtained from the original FNRI formulation and procedure were improved through the addition of flavoring to and the optimization of drying and frying conditions. Its market acceptability was determined using a central location test. Marketing, technical and financial studies were prepared as party of pre-investment studies. A six-week accelerated shelf-life testing was also conducted using PE-laminated Aluminum foil as packaging material. Results of the product improvement indicated that the optimum level of barbecue flavoring to be added is at 5% w/w basis. The optimum drying conditions were at 50°C for 5 hours and at 60°C for 4 hours. A 185-190°C frying temperature for a duration of 10-20 seconds yielded a desirable final product. On the other hand, market acceptability testing among 60 children between 5-15 years old indicated that the product was acceptable, with 87% of the respondents actually liking the product. Accelerated shelf-life testing showed that for samples stored at 11%, 43% and 73% RH, the product remained crisp and free from rancid flavor for the six weeks storage period. At 100% RH, crispness decreased to a considerable extent but no rancid flavor was detected by the panelists. TBA values obtained at the end of the storage period revealed that lipid oxidation had not yet occurred to a great extent in the stored sample